Basic cancer immunology for radiation oncologists. Issue 4 (29th March 2022) - Sia, Joseph; Neeson, Paul J; Haynes, Nicole M
Summary: Although the impressive clinical responses seen with modern cancer immunotherapy are currently limited to a subset of patients, the underlying paradigm shift has resulted in now hardly a segment in oncology that has not been touched by the immuno‐oncology revolution. A growing body of data indicates that radiation therapy (RT) can modulate the tumour immune microenvironment and complement cancer immunotherapy via non‐overlapping mechanisms to reinvigorate immunity against cancer. Thus, increasingly RT is viewed as a highly unique partner for immunotherapy across the spectrum of cancer settings, as radiobiology and cancer immunology foreseeably become more intertwined. Considering these developments, this review summarises the key concepts and terminology in immunology for the radiation oncologist, with a focus on the cancer setting and with reference to important recent advances. These concepts will provide a starting point for understanding the strategies that underlie current and emerging immunotherapy trials, as well as the indirect effects of RT by which immune responses against cancer are shaped.